TINGKAT KEBERHASILAN GAPOKTAN DHARMA PERTIWI DESA LUKLUK DAN GAPOKTAN CAKRA BUANA DESA KUWUM DI KECAMATAN MENGWI KABUPATEN BADUNG DALAM MENERAPKAN TEKNOLOGI PROGRAM SIMANTRI BERBASIS SAPI BALI - Putri Dwi Susanthi; N. K. Nuraini; I G. Suarta (Jurnal Peternakan Tropika, 2014)
The successful implementation technology of Simantri is a state that describes the extent to which Gapoktan Simantri have successfully achieved the goal or expectation Simantri program implementation, as measured by the succesfull implementation Simantri indicator. This study aimed to determine the success rate Gapoktan Dharma Pertiwi and Cakra Buana in applying technology of  Simantri and knowing the factors that can affect the success in applying technology Simantri. The research was conducted in Lukluk and Kuwum villages, Mengwi district, Badung  regency, Bali. Data collection was conducted using a survey of 40 respondents using a questionnaire research instruments . Data were analyzed using qualitative descriptive analysis, the Wilcoxon signed rank sum test levels, tiered Spearman correlation coefficient. The results showed that: 1 ) the percentage score Gapoktan Dharma Pertiwi Lukluk Village success rate was 75,17 % (category successfully) and the success rate Gapoktan Cakra Buana Kuwum village is 68,04 % (category successfully) highly significant (P<0,01 ); 2) In Gapoktan Dharma Pertiwi knowledge factors have a very significant relationship (P<0,01), whereas other factors such as the skills, attitudes, goals, motivation and intensity of communication each have a real relationship (P<0,05) with the level of success in applying technology of Simantri in Gapoktan Dharma Pertiwi and Gapoktan Cakra Buana